PROGRAM POLICY IMPLEMENTATION CHILD FRIENDLY DISTRICT - Katili, Andi Yusuf; Rachman, Ellys; Gobel, Lisda Van (Universitas Negeri Gorontalo, 2023)
This study aims to analyze the extent to which the implementation of the child-friendly district program is carried out in accordance with the statements in regional regulations, especially in Gorontalo Regency. The research method used is qualitative descriptive. Data sources are derived from primary and secondary data. Data collection techniques are obtained through observation, interviews, and documentation. Protection of children is an obligation of parents without discrimination because children need to live better wherever they are and must be guaranteed by all families and social environments, especially their parents. Children are vulnerable to violence, both from their age and from adult disorders. Violence against children, both women and men can occur in various environments, both in families, schools, and outside the home. Therefore, attention to child safety must be a priority carried out by parents, families and also the government, where it has been regulated or has official regulations in the form of law number 35 of 2014 so that no one can avoid criminal threats if there is violence against a child, it must be punished in accordance with applicable regulations. The results showed that the implementation of the Child decent District program policy in Gorontalo Regency has not been optimal due to low socialization carried out by the local government, lack of coordination between related agencies, and supervision of officers by agencies has not been effective, and efficient due to the lack of officers (HR), as well as inadequate facilities and infrastructure.